Effects of Social-Cognitive Processing Demands and Structural Importance on Narrative Recall: Differences Between Children, Adolescents, and Adults. Issue 5 (3rd July 2016) - Pavias, Marcella; van den Broek, Paul; Hickendorff, Marian; Beker, Katinka; Van Leijenhorst, Linda
Abstract : This study examined the contributions of developmental changes in social-cognitive ability throughout adolescence to the development of narrative comprehension. We measured the effects of sensitivity to the causal structure of narratives and of sensitivity to differences in social-cognitive processing demands on narrative recall by children (8–10 years old), adolescents (13–15 years old), and adults (19–21 years old). Generalized mixed-effects models for dichotomous variables revealed that social-cognitive processing demands of story elements predicted differences in narrative recall between the age groups, over and above the causal importance of story elements. Children's and adolescents' recall of the narrative differed from that of adults, and these differences were most apparent for social-cognitive aspects of the narrative. These findings suggest that immature social-cognitive abilities limit narrative comprehension in childhood and adolescence and, in doing so, contribute to our understanding of the interaction between reader characteristics and text characteristics in the development of narrative comprehension.